1962
DOI: 10.1139/m62-059
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Gamma Radiation for the Preparation of Virus Vaccines

Abstract: A protective agent such as histidine or sodium p-aminohippurate was added to purified suspensions of influenza and mumps viruses. It was then possible to inactivate them in about an hour with gamma radiation while retaining most of the hemagglutination titer. It was demonstrated in mice that a vaccine prepared from a mouse-adapted virus (Shope's swine influenza strain of influenza A) conferred protection against challenge by the live virus and produced an antibody response as measured by the hemagglutination–i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1967
1967
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…It has been reported that y-rays inactivate the viruses of poliomyelitis, St. Louis encephalitis, western equine encephalitis (1), vaccinia (1,2), influenza, and mumps (6). The results presented suggest that this method of inactivation destroys the capacity of the virus to produce infectivity in animals, but it does not alter the antigenicity unless large doses of radiation are employed.…”
mentioning
confidence: 83%
“…It has been reported that y-rays inactivate the viruses of poliomyelitis, St. Louis encephalitis, western equine encephalitis (1), vaccinia (1,2), influenza, and mumps (6). The results presented suggest that this method of inactivation destroys the capacity of the virus to produce infectivity in animals, but it does not alter the antigenicity unless large doses of radiation are employed.…”
mentioning
confidence: 83%
“…A number of viruses capable of infecting man have been isolated from food and food animals (1,2,4,5,9,11,12,16,20,22,23,29,31), and extensive studies on viral inactivation by gamma radiation have been reported (3,6,7,15,18,19,24,25,(26)(27)(28). However, only one investigation dealt with inactivation of viruses in food processing.…”
mentioning
confidence: 99%
“…The X rays and gamma rays that are used for inactivation are short wavelength electromagnetic radiations that have high penetrating ability and have the desired characteristic of not imparting radioactivity to the exposed material. Studies with bacterial and animal viruses have shown that infectivity of viruses may be selectively destroyed by radiation while leaving antigenicity intact (4,7,11).…”
mentioning
confidence: 99%